Regional foreign banks and financial inclusion: Evidence from Africa - (:unkn) unknown (My University, 2020)
Regional foreign banks expanded quickly over the past decade in developing and emerging countries and have a growing influence in banking systems. We question whether the development of African regional foreign banks, also called Pan-African banks, influences financial inclusion of firms and households. To this end, we combine the World Bank Global Findex database and the World Bank Enterprise Surveys with a hand-collected database on the presence of regional foreign banks. We find that Pan-African banks presence increases firms’ access to credit and limited evidence that they favor financial access of the middle class by restoring confidence in banks. We suggest that this impact is related to the adoption of an aggressive strategy aiming at gaining market shares rather than through the exploitation of informational and technological advantages.
Keywords: African Research